The Influence of Perceived Ease, Perceived Benefit, and Sales Promotion on Purchasing Decisions on the Shopee Marketplace - Taqiyyah, Nada; Bertuah, Eka (Yayasan Gema Bina Nusantara, 2025)
The purpose of this study was to investigate the direct influence of Perceived Ease, Perceived Benefits and Sales Promotion on Purchasing Decisions, to determine the direct influence of Perceived Ease, Perceived Benefits and Sales Promotion on Purchasing Decisions. As well as the joint influence of Perceived Ease, Perceived Benefits and Sales Promotion on Purchasing Decisions of Shopee marketplace consumers. Data collection was carried out using a questionnaire distributed online using Google Form via social media, such as Whatsapp and Instagram. The population in this study were all Shopee users in the Jabodetabek area. The questionnaires collected were 160 respondents and the data was processed using multiple regression analysis tools. From the results of the study, it was found that Perceived Ease influenced Purchasing Decisions. Perceived Benefits had a positive influence on Purchasing Decisions. Sales Promotions did not influence Purchasing Decisions, and Perceived Ease, Perceived Benefits and Sales Promotions had a joint influence on Purchasing Decisions.